Interaction of a System of Four Particles through a Random Unique Source - MASSOU, SIAKA; MOUSSILIOU, Sikirou; ESSOUN, ADÉBAYO LOUIS; TCHOFFO, Martin (My University, 2012)
To this purpose, one uses the result that quantum phenomena in the Euclidean formulation of the theory are due to a stochastic space-time background interaction, whose essence is the time derivative of the Wiener process. The problem of calculating both the transition probability, the path integral for the systems of four particles and factorization solution of Fokker-Planck equation are then solved. The transition probability solution of Fokker-Planck equation factorizes into a first component describing the system at its ground state and a second component characterizing its transition dynamics. The path integral for these system are then solved
Keywords: wiener process; Fokker-Planck equation; path integral; transition probability density; theorem of; factorization